The discomfort of evening : a novel - Rijneveld, Marieke Lucas (Graywolf Press, 2020)
Jas is a girl whose brother's death punctures the routines of her devout farming family. In the vacuum of their parents' own unraveling, Jas and her siblings develop a curiosity about death that leads them into increasingly disturbing rituals and fantasies.